The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.7439/ijbar.v3i6.508
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Calcium and Serum Magnesium Level in Preeclamptic vs Normal Pregnancy

Abstract: Objective: To compare serum calcium and magnesium in preeclamptic women and normal pregnant women. Materials and methods: A cross sectional study was done between August 2010 to April 2011 on 30 normal pregnant women and 30 preeclamptic women in Dhiraj Hospital attended Gynecology and Obstetrics' department. The blood samples were collected and analyzed for calcium and magnesium by semi-automatic analyzer ERBA CHEM 5 in central laboratory. The data was analyzed using SPSS version 15. The p-value <0.05 was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 12 publications
5
14
1
Order By: Relevance
“…The Mean ± SD of gestational ages of the preeclamptic women and the normal healthy women are significantly different as is shown in Table 1. The present study showed a Mean ± SD of 36.38 ± 4.19 weeks in cases and 39.62 ± 1.16 weeks in controls with a highly significant p-value of < 0.001, which correlates with the study of Deepa V Kanagal et al (8) and of Harma et al, (9) Farah Saleh et al (10) and Chaurasia et al (11) Mean ± SD of systolic BP (153±19.39 mmHg vs. 109.6±7.55 mmHg) and Mean ± SD of Diastolic BP (102.4±13.99 mmHg vs. 75.4±5.30 mmHg) of the preeclamptic group are significantly higher than the control group (p < 0.001) as shown in Table 2, which correlates well with the study of Rubina Aziz et al (12) and also with the study of Deepa V Kanagal et al (8) and Farah Saleh et al (10)…”
Section: Discussionsupporting
confidence: 91%
“…The Mean ± SD of gestational ages of the preeclamptic women and the normal healthy women are significantly different as is shown in Table 1. The present study showed a Mean ± SD of 36.38 ± 4.19 weeks in cases and 39.62 ± 1.16 weeks in controls with a highly significant p-value of < 0.001, which correlates with the study of Deepa V Kanagal et al (8) and of Harma et al, (9) Farah Saleh et al (10) and Chaurasia et al (11) Mean ± SD of systolic BP (153±19.39 mmHg vs. 109.6±7.55 mmHg) and Mean ± SD of Diastolic BP (102.4±13.99 mmHg vs. 75.4±5.30 mmHg) of the preeclamptic group are significantly higher than the control group (p < 0.001) as shown in Table 2, which correlates well with the study of Rubina Aziz et al (12) and also with the study of Deepa V Kanagal et al (8) and Farah Saleh et al (10)…”
Section: Discussionsupporting
confidence: 91%
“…The mean serum calcium did not differ significantly between the subjects of pre-eclampsia and normal pregnant women (p=0.963). This was in contrast with several studies, 5,6,[13][14][15] suggesting hypocalcemia as a possible cause for preeclampsia. All theses study reported significantly lower calcium in pre-eclamptic patients than normal pregnancy.…”
Section: Discussioncontrasting
confidence: 99%
“…So the modification of calcium metabolism during pregnancy could be one of the causes of pre-eclampsia [10][11] . Several studies showed that significantly low serum calcium level in pre-eclamptic women as compare to normal pregnant (p<0.05) [12][13][14][15][16] . But in other studies serum levels of calcium did not differ significantly between pre-eclamptics and comparative group 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…sodium potassium ATPase) and involved in peripheral vasodilatation. 2,9,10 Some studies shows that blood calcium and magnesium have a relaxant effect on the blood vessels of pregnant women. 9,11 Aims and objectives…”
Section: Introductionmentioning
confidence: 99%